Control of Wilt and Rot Pathogens of Tomato by Antagonistic Pink Pigmented Facultative Methylotrophic Delftia lacustris and Bacillus spp. - Janahiraman, Veeranan; Anandham, Rangasamy; Kwon, Soon W.; Sundaram, Subbiah; Karthik Pandi, Veeranan; Krishnamoorthy, Ramasamy; Kim, Kiyoon; Samaddar, Sandipan; Sa, Tongmin (Frontiers in Plant Science, 2016)
The studies on the biocontrol potential of pink pigmented facultative methylotrophic (PPFM) bacteria other than the genus Methylobacterium are scarce. In the present study, we report three facultative methylotrophic isolates; PPO-1, PPT-1 and PPB-1, respectively identified as Delftia lacustris, Bacillus subtilis and Bacillus cereus by 16S rRNA gene sequence analysis. Hemolytic activity was tested to investigate the potential pathogenicity of isolates to plants and humans, the results indicates that the isolates PPO-1, PPT-1 and PPB-1 are not pathogenic strains. Under in vitro conditions, D. lacustris PPO-1, B. subtilis PPT-1 and B. cereus PPB-1 showed direct antagonistic effect by inhibiting the mycelial growth of fungal pathogens; Fusarium oxysporum f. sp. lycopersici (2.15, 2.05 and 1.95 cm), Sclerotium rolfsii (2.14, 2.04 and1.94 cm), Pythium ultimum (2.12, 2.02 and 1.92cm), and Rhizoctonia solani (2.18, 2.08 and 1.98 cm) and also produced volatile inhibitory compounds. Under plant growth chamber condition methylotrophic bacterial isolates; D. lacustris PPO-1, B. subtilis PPT-1 and B. cereus PPB-1 significantly reduced the disease incidence of tomato. Under greenhouse condition, D. lacustris PPO-1, B. subtilis PPT-1 and B. cereus PPB-1 inoculated tomato plants, when challenged with F. oxysporum f. sp. lycopersici, S. rolfsii, P. ultimum and R. solani, increased the pathogenesis related proteins (β-1, 3-glucanase and chitinase) and defense enzymes (phenylalanine ammonia lyase, peroxidase, polyphenol oxidase, and catalase) on day 5 after inoculation. In the current study, we first report the facultative methylotrophy in pink pigmented Delftia lacustris, B. subtilis, and B. cereus and their antagonistic potential against fungal pathogens. Direct antagonistic and ISR effects of these isolates against fungal pathogens of tomato evidenced their possible use as a biocontrol agent.